INVESTIGATION OF BIOLOGICAL PROPERTY FEATURES VARIABILITY OF CANDIDA FAMILY YEAST-LIKE FUNGI (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The purpose of investigation was to study cultural and proteolytic properties of candida family yeast-like fungi. It is stated, that natural variability of C.albicans colonies morphology depends on storage period of strains and amount of passages. Besides typical S and atypical K forms, R forms can appear both at collectional, and at hospital strains. Negative results on proteolytic activity are determined for collectional strains in the third passage, for hospital strains in the first passage.